Is there any relationship between ABO/Rh blood group and patients with pre-eclampsia? - Hentchke, Marta; Caruso, Fernanda B.; Paula, Letícia G.; Medeiro, Augusto K.; Gadonski, Giovani; Antonello, Ivan C.; Mistry, Hiten D.; Poli-de-Figueiredo, Carlos; Pinheiro da Costa, Bartira (Elsevier, 2014)
Objectives: The purpose of the present study was to evaluate the association between pre-eclampsia and blood groups in a group of pregnant women hospitalized in a University Hospital in Porto Alegre, Brazil -Hospital São Lucas (HSL)/PUCRS. Study design: Our sample consisted of 10.040 pregnant women admitted to the maternity department of HSL between 2005 and 2010. The patients were reviewed retrospectively for inclusion. Medical records of 414 women were diagnosed as preeclampsia/eclampsia and were identified 9611 women to the control group. The patients were divided into two groups: the group with preeclampsia/eclampsia and the control group, and their blood groups were considered. Data were analyzed using SPSS for Windows version 17.0. Categorical data were summarized by counts and percentages, with the statistical significance evaluated by the Chi-square test. The null hypothesis was rejected when p<0.05. Main outcome measures: Maternal parameters were compared between control group and pre-eclampsia, respectively, Systolic Blood Pressure (117±19,98 vs. 165±19,99); Diastolic Blood Pressure (73±14,23 vs. 106±14,24) and maternal weight at booking (73± 33 vs. 83± 33). For all data: mean+SD; P<0.05. In relation to blood groups, firstly they were stratified by Rh and ABO phenotypes, separately. After that the groups were stand together Results: No differences in blood group distribution were observed between controls and pre-eclampsia for any analysis. (p>0.05). Conclusions: When we adopted stricter criteria for pre-eclampsia and a large sample from the same region we noted that the results did not show any association between blood groups and the development of pre-eclampsia.